Angular extension of io magnetic footprint in response to Io’s locations - Wannawichian S. (2017)
© 2016, Chiang Mai University. All rights reserved. FUV images of Jupiter’s auroral region have been taken since the early observational era of the Hubble Space Telescope (HST) by the Space Telescope Imaging Spectrograph (STIS). In the vicinity of the main auroral oval, an emission spot was detected and appeared to be evidence of electromagnetic interaction between Jupiter’s magnetospheric plasma and Io’s atmosphere. In previous works, the brightness of this emission, which is called Io’s auroral magnetic footprint, reveals strong correlation with Io’s location in Jupiter’s system III longitude. In this study, the magnetic footprint emissions were chosen regarding the variation of Io’s locations. Detailed analysis of the angular extension of Io’s magnetic footprint was presented. Based on the complexity of angular extension due to the multiplicity of the footprint spots, it was found that the angular extension increases when Io is moving closer to the torus center. This result suggests the possible influence of the picked-up current on the extension of the interaction region between precipitating electrons and Jupiter’s ionospheric particles.